2000
DOI: 10.1055/s-2000-6373
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Methylation of Aryl Chlorides by Stabilized Dimethylaluminium and -Gallium Reagents

Abstract: Two methods for palladium-catalyzed cross-methylation of aryl chlorides by intramolecularly stabilized dialkylaluminium and -gallium complexes 6-13 have been studied. In one method, in which either tetrakis(triphenylphosphine)palladium (1) or dichlorobis(triphenylphosphine)palladium (2) is used as the catalyst at 80-90°C, the activation of the chlorine atom is affected by introduction of strong electron-withdrawing groups into the aromatic moiety. The second method is based on the application of either [1,3-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 10 publications
1
22
0
1
Order By: Relevance
“…Selective cleavage of a strong bond by a late‐transition metal in the presence of a weaker one is rare 4h. 5b, 24 In addition, no metal transfer was observed during the formation of complex ${{\bf 3}{{{\rm \bf Br}\hfill \atop = \hfill}}}$ from ${{\bf 2}{{{\rm \bf Br}\hfill \atop = \hfill}}}$ in the presence of PhBr …”
Section: Resultsmentioning
confidence: 99%
“…Selective cleavage of a strong bond by a late‐transition metal in the presence of a weaker one is rare 4h. 5b, 24 In addition, no metal transfer was observed during the formation of complex ${{\bf 3}{{{\rm \bf Br}\hfill \atop = \hfill}}}$ from ${{\bf 2}{{{\rm \bf Br}\hfill \atop = \hfill}}}$ in the presence of PhBr …”
Section: Resultsmentioning
confidence: 99%
“…Blum et al have recently shown that aryl chlorides can be methylated by hypervalent aluminum and gallium complexes 165. [Pd(PPh 3 ) 4 ] is an acceptable catalyst for highly activated nitro‐substituted aryl chlorides, but the palladium complex of a bulky, electron‐rich, chelating ligand such as 1,3‐bis(diisopropylphosphanyl)propane (dippp) is required for electron‐neutral substrates.…”
Section: Carbon–carbon Bond‐forming Reactionsmentioning
confidence: 99%
“…Blum et al zeigten, dass Arylchloride durch hypervalente Aluminium‐ und Galliumkomplexe methyliert werden können 165. Für hochaktivierte nitrosubstituierte Arylchloride ist [Pd(PPh 3 ) 4 ] ein akzeptabler Katalysator, doch für elektronenneutrale Substrate ist der Palladiumkomplex eines voluminösen, elektronenreichen chelatbildenden Liganden wie 1,3‐Bis(diisopropylphosphano)propan (dippp) nötig.…”
Section: Reaktionen Zur Knüpfung Von Kohlenstoff‐kohlenstoff‐binduunclassified